Analisis Risk Management Pada Pembangunan Kekuatan TNI AL - Syahputra, Firman; Komaruddin, Komaruddin; Darmawan, Budi (Universitas Pahlawan Tuanku Tambusai, 2024)
Risk management in the context of building the strength of the Indonesian Navy is a crucial element that influences the success and sustainability of their strategic projects. In an effort to understand and manage risk more effectively, this research was conducted with the aim of exploring the risk management practices implemented by the Indonesian Navy in building their force. The research method used is a qualitative approach using interviews as the main data collection technique. The background to this research involves the complexity and high risks associated with military projects, including technical, environmental, and security risks. The aim of this research is to identify best practices in risk management that can be applied in the context of building Indonesian Navy forces, as well as to evaluate the effectiveness of existing mitigation strategies. The results of this research show that the risk identification process was carried out comprehensively by considering various factors such as technical, environmental and security analysis. Risk evaluation is carried out by involving various stakeholders to ensure a deep understanding of the probability of risk occurrence and its impact on project objectives. Effective mitigation strategies are based on the use of advanced technology, careful planning, and close collaboration between the Indonesian Navy, contractors and other related parties.